Critical Perspectives on Interreligious Education Experiments in Empathy - Syeed, Najeeba (Currents of Encounter, 2020)
In Experiments in Empathy: Critical Reflections on Interreligious Education, the contributors provide a roadmap for practicing and developing innovative ways to teach religion that promotes interfaith understanding and cooperation. Readership: All interested in interreligious education, interfaith movement, comparative theologies, religious education, religion and politics will find Experiments in Empathy of great use and interest.